1990
DOI: 10.1148/radiology.174.2.2296645
|View full text |Cite
|
Sign up to set email alerts
|

Use of magnetite particles as a contrast agent for MR imaging of the liver.

Abstract: To evaluate the potential of dextran-coated magnetite (DM) particles in enhancing the detection of hepatocellular carcinoma with magnetic resonance (MR) imaging, the authors induced liver tumors in rats by oral administration of diethylnitrosamine and examined the rats before and after intravenous injections of DM with various iron concentrations. Because of the intense and preferential T2 relaxativity of DM, use of DM with an iron concentration of 10 mumol/kg yielded effective MR signal reduction in each norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…It has been shown that a negative charge on the particle surface accelerates phagocytosis (22). The surface of carboxylate-modified latex beads is negatively charged due to a hydroxyl group (-OH) (23), and SPIOs are also negatively charged by the hydroxyl group of dextran (24). The selected size and surface structure of latex beads were analogous to SPIO, and it was expected that RES phagocytosis of latex beads could simulate that of SPIO (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a negative charge on the particle surface accelerates phagocytosis (22). The surface of carboxylate-modified latex beads is negatively charged due to a hydroxyl group (-OH) (23), and SPIOs are also negatively charged by the hydroxyl group of dextran (24). The selected size and surface structure of latex beads were analogous to SPIO, and it was expected that RES phagocytosis of latex beads could simulate that of SPIO (22).…”
Section: Discussionmentioning
confidence: 99%
“…The selected size and surface structure of latex beads were analogous to SPIO, and it was expected that RES phagocytosis of latex beads could simulate that of SPIO (22). Thus, we used intravital microscopy using latex beads (10 -11) instead of previously used histologic iron staining after SPIO injection for animals (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the functional properties of the magnetic nanoparticles have been modified individually so that they could be used in different biological applications, such as cell label and separation [4][5][6][7], immunoassay [8,9], drug delivery [10][11][12], MRI contrast agents [13][14][15][16][17][18], and hyperthermia [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Eisenoxidpartikel besitzen darüber hinaus adsorptive Eigenschaften und können die Toxizität, die Aufnahme und den Metabolismus adsorbierter Stoffe infolge Kombinationswirkung beeinflussen (u. a. Cheu et al 1996;Garcon et al 2000;Haguenoer et al1996 (Kawamura et al 1990). …”
Section: Analytische Bestimmung (Verfahrenshinweise)unclassified